2017
DOI: 10.22178/pos.25-5
|View full text |Cite
|
Sign up to set email alerts
|

Cash-Cow into the Purse of Malaysian Property Investors: Students Housing Investment

Abstract: Abstract. Growing demand for higher education (HE) and increasing students enrolment in higher education institutions (HEI) has been a global issue especially in the last three decades and housing the growing student population has become a dilemma for all concern HEIs stakeholders. Globally increasing demand for HE and enrolment has long been not corresponding with student housing supply. Most HEIs provide housing accommodation for a small proportion of their total students' population while the majority depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…According to [44] survey of 20 private students house developers in USA found that, in 2015 alone, these companies have over 167 student properties under construction comprising 97,045 beds. This is because, it is a distinct niche market for private developers and home-owners more especially those who would target areas adjacent to HIs campuses [6,8,12,36] hence, the waves of student demand tells much about the likelihood of the better place of opportunity.…”
Section: Student Housing Related Studiesmentioning
confidence: 99%
“…According to [44] survey of 20 private students house developers in USA found that, in 2015 alone, these companies have over 167 student properties under construction comprising 97,045 beds. This is because, it is a distinct niche market for private developers and home-owners more especially those who would target areas adjacent to HIs campuses [6,8,12,36] hence, the waves of student demand tells much about the likelihood of the better place of opportunity.…”
Section: Student Housing Related Studiesmentioning
confidence: 99%
“…Studentification is a significant process of urban change, tied to growing concentrations of university students, that has widely penetrated national public debates and policy‐orientated agendas during the last two decades (Moos et al., ; Nakazawa, ). As a highly contentious societal and economic issue (He, ; Holton, ), studentification is often represented in negative ways in pejorative media discourses across the globe, including Australia (Ruming & Dowling, ), China (Zhao & Zou, ), Hungary (Fabula et al., ), Malaysia (Ghani & Suleiman, ), South Africa (Ackermann & Visser, ), Spain (Garmendia et al., ) and the United States (Foote, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant driver of student housing demand in the off-campus rental market. This group of students has matured students who required more freedom, privacy and noise-free environment away from the core students' area [14]. They study for a more extended period and place a high value on privacy, therefore, will not likely share a room.…”
Section: "You Know Here In Malaysia; We Have Different Accommodationsmentioning
confidence: 99%